A hard carbon-silicon carbon composite material and its preparation method and application
By covering hard carbon on the surface of the silicon-based material and depositing silver to form a hard carbon-silicon carbon composite material, the problems of low efficiency of hard carbon materials and large expansion of silicon-carbon materials in the prior art are solved, and high energy density and good cycling performance are achieved.
Patent Information
- Application Number
- CN202211216754.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-30
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2042-09-30
AI Technical Summary
The existing hard carbon materials have low first-time efficiency, high expansion and poor low-temperature performance, resulting in problems with energy density and cycling performance in their application in lithium-ion batteries.
By coating hard carbon on the surface of the silicon-based material, forming a core-shell structure, and depositing silver by electrochemical deposition, the electron conductivity is improved, thereby improving energy density and power performance.
It achieves the reduction of the expansion rate of the material while ensuring high energy density, and significantly improves the circulation and storage performance of the material.
Smart Images

Figure CN115483384B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of lithium ion battery materials, and in particular relates to a hard carbon-silicon carbon composite material and a preparation method and application thereof. Background Art
[0002] Hard carbon materials are used in 48V, HEV and sodium-ion batteries due to their advantages of zero expansion, excellent low-temperature performance and fast charging performance. However, due to the porous structure, zero expansion, excellent low-temperature performance and high specific surface area of hard carbon, the initial efficiency of the material is low (about 80%), and the specific capacity is about 300mAh / g, which is much lower than the specific capacity of graphite (355mAh / g) and the specific capacity of silicon oxide (1600mAh / g).
[0003] Although silicon-carbon materials have high specific capacity (nano-silicon is about 3000 mAh / g), they have high expansion (up to about 150%) and poor low-temperature performance, resulting in deviations in their normal temperature cycle and low-temperature cycle performance.
[0004] Therefore, the prior art attempts to combine the two materials in order to compensate for the defects of the other material with the advantages of one material. However, the preparation method of the composite material has many factors that affect the performance of the composite material and also brings other problems. Summary of the invention
[0005] In order to solve the shortcomings of the prior art, the present invention provides a hard carbon-silicon carbon composite material. To address the current problems of hard carbon energy density and large silicon carbon expansion, hard carbon is coated on the surface of a silicon-based material to form a composite material, and silver is deposited to improve electronic conductivity, energy density and power performance.
[0006] In order to achieve the above technical objectives, the technical solution adopted by the present invention is as follows:
[0007] The technical purpose of the first aspect of the present invention is to provide a hard carbon-silicon carbon composite material having a core-shell structure, wherein the core comprises Si / SiO x and an amorphous carbon component, wherein the outer shell is hard carbon doped with metallic silver, and the mass percentage of the outer shell is 10-60% based on the total weight of the composite material.
[0008] Furthermore, based on the total weight of the core, Si accounts for 5-20%, SiO x It accounts for 5-20%, and the rest is amorphous carbon.
[0009] Furthermore, based on the total weight of the composite material, the doping amount of silver is 0.1-0.5%, preferably 0.15-0.45%, and the rest is hard carbon.
[0010] The technical purpose of the second aspect of the present invention is to provide a method for preparing a hard carbon-silicon carbon composite material, comprising the following steps:
[0011] Preparation of core: Prepare organic solvent dispersion of nano-silicon, add aminosilane coupling agent and dispersant, adjust pH to 8-10 with ammonia water, spray dry, sinter under inert atmosphere, and crush to obtain Si / SiO x and an inner core of an amorphous carbon component;
[0012] Shell coating: preparing an aqueous solution of sodium lignin sulfonate and starch, adding the prepared core material, dispersing, hydrothermal reaction, filtering, carbonizing, and obtaining a composite of a hard carbon-coated core;
[0013] Silver doping: Using ethylene glycol solution of silver salt as solvent and saturated calomel as reference electrode, the hard carbon-coated core composite is pressed on aluminum foil as working electrode, and electrochemical deposition is performed by constant voltage method, followed by washing, drying and crushing to obtain the hard carbon-silicon carbon composite material.
[0014] Furthermore, when preparing the inner core, the mixing ratio of nano silicon, organic solvent, silane coupling agent and dispersant is 100g:1000-2000mL:100-200g:1-5g.
[0015] Furthermore, when preparing the inner core, the organic solvent used is at least one selected from ethanol, isopropanol, propylene glycol, butylene glycol and isopropanol.
[0016] Furthermore, the aminosilane coupling agent is selected from at least one of aminopropyltrimethoxysilane, aminopropyltriethoxysilane and aminopropylmethyldiethoxysilane.
[0017] Furthermore, the dispersant is selected from at least one of hexadecyltrimethylammonium bromide, tridecyl polyoxyethyl ether and dodecyldimethylbenzyl ammonium chloride.
[0018] Furthermore, when coating the shell, the mass concentration of starch in the solution is 1-10%, and the mass ratio of sodium lignin sulfonate, starch and core material is 5-30:5-30:50.
[0019] Furthermore, the temperature of the hydrothermal reaction is 100-200°C, the pressure is 1-5Mpa, and the reaction time is 1-6h.
[0020] Furthermore, the carbonization temperature is 900-1200° C. and the time is 1-6 hours.
[0021] Furthermore, the silver salt is selected from one of silver nitrate, silver carbonate and silver sulfate.
[0022] Furthermore, the mass volume concentration of silver in the ethylene glycol solution of the silver salt is 1-10 g / 100 mL.
[0023] Furthermore, the voltage of the electrochemical deposition is 2V, and the deposition time is 60-600s.
[0024] Furthermore, the cleaning is firstly cleaning with dilute hydrochloric acid (such as a concentration of 0.5-1.2 mol / L) and then cleaning with deionized water.
[0025] Furthermore, the drying is vacuum drying.
[0026] The third aspect of the present invention is to provide the application of the hard carbon-silicon-carbon composite material or the hard carbon-silicon-carbon composite material prepared by the preparation method as a negative electrode material for a battery. Specifically, the battery is a lithium ion and / or sodium ion battery.
[0027] Implementing the embodiments of the present invention will have the following beneficial effects:
[0028] (1) The present invention forms a three-dimensional structure by adding an aminosilane coupling agent to a nano-silicon solution and carbonizing the solution. The aminosilane coupling agent generates porous nitrogen-containing amorphous carbon and silicon-oxygen compounds, which react with the nano-silicon to form a nano-silicon / silicon-oxygen / amorphous carbon composite with a porous structure. While ensuring high energy density, the expansion rate of the material is also low.
[0029] (2) Sodium lignin sulfonate is added to the outer shell of the present invention, and the amorphous carbon formed after carbonization has a large interlayer spacing, which improves the insertion and extraction ability of sodium ions / lithium ions and the defects left behind, and the amorphous carbon formed by starch carbonization is used to compensate and improve the sodium / lithium storage capacity; silver is deposited on the outer layer and filled in the hard carbon pores to improve the electronic conductivity of the material and improve the rate performance.
[0030] (3) The present invention uses an electrochemical deposition method to deposit silver, which has the characteristics of high density, strong structural stability of the material under high voltage, and high compatibility with organic electrolytes. When used in lithium batteries, it can improve the cycle and storage performance.
[0031] In order to make the concept and other purposes, advantages, features and functions of the present invention more clearly understood, preferred embodiments will be specifically cited in the following specific implementation manner and described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0033] in:
[0034] Figure 1 This is the SEM image of the hard carbon-silicon carbon composite material prepared in Example 1. DETAILED DESCRIPTION
[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] In Examples 1-3, a hard carbon-silicon carbon composite material was prepared:
[0037] Example 1
[0038] S1, preparation of the core: 100 g of nano-silicon was added to 1500 mL of isopropanol and dispersed evenly to obtain a suspension, then 150 g of aminopropyltrimethoxysilane and 3 g of hexadecyltrimethylammonium bromide were added and dispersed evenly, the pH was adjusted to 9 with ammonia water, spray dried, sintered at 800 ° C for 3 h, and crushed to obtain Si / SiO x and an inner core of an amorphous carbon component;
[0039] S2, shell coating: 20 g of sodium lignin sulfonate was added to 400 mL of 5 wt% starch aqueous solution, and then the core prepared in S1 was added. After uniform dispersion, it was transferred to a high-pressure reactor, and a hydrothermal reaction was carried out at a temperature of 150°C and a pressure of 3 MPa for 3 h. The mixture was filtered and carbonized at a temperature of 1000°C for 3 h to obtain a composite of a hard carbon-coated core.
[0040] S3, silver doping: add 10g of silver nitrate to 200mL of ethylene glycol solution to prepare an ethylene glycol solution of silver nitrate with a mass volume concentration of 5g / 100mL and use it as a solvent, saturated calomel is used as a reference electrode, and the hard carbon-coated core composite prepared in S2 is pressed on aluminum foil as a working electrode. The constant voltage method (voltage 2V) is used for electrochemical deposition for 120s, and then it is washed with 0.1mol / L hydrochloric acid, washed with deionized water, vacuum dried at 80°C for 24h, and crushed to obtain the hard carbon-silicon carbon composite material.
[0041] Example 2
[0042] S1, preparation of the core: 100 g of nano-silicon was added to 1000 mL of propylene glycol and dispersed evenly to obtain a suspension, then 100 g of aminopropyl triethoxysilane and 1 g of tridecyl polyoxyethyl ether were added and dispersed evenly, the pH was adjusted to 8 with ammonia water, spray dried, sintered at 800 ° C for 3 h, and crushed to obtain Si / SiO x and an inner core of an amorphous carbon component;
[0043] S2, shell coating: 5 g of sodium lignin sulfonate was added to 500 mL of 1 wt% starch aqueous solution, and then the core prepared in S1 was added. After uniform dispersion, it was transferred to a high-pressure reactor and subjected to hydrothermal reaction at a temperature of 100 ° C and a pressure of 5 MPa for 6 h. The mixture was filtered and carbonized at a temperature of 900 ° C for 6 h to obtain a composite of a hard carbon-coated core.
[0044] S3, silver doping: add 10g of silver nitrate to 1000mL of ethylene glycol solution to prepare an ethylene glycol solution of silver nitrate with a mass volume concentration of 1g / 100mL and use it as a solvent, saturated calomel as a reference electrode, and the hard carbon-coated core composite prepared in S2 is pressed on aluminum foil as a working electrode. A constant voltage method (voltage 2V) is used for electrochemical deposition for 60s, followed by washing with 0.1mol / L hydrochloric acid, washing with deionized water, vacuum drying at 80°C for 24h, and crushing to obtain the hard carbon-silicon carbon composite material.
[0045] Example 3
[0046] S1, preparation of the core: 100 g of nano-silicon was added to 2000 mL of isopropanol and dispersed evenly to obtain a suspension; then 200 g of aminopropylmethyldiethoxysilane and 5 g of dodecyldimethylbenzyl ammonium chloride were added and dispersed evenly, and the pH was adjusted to 10 with ammonia water, spray dried, sintered at 800 ° C for 3 h, and crushed to obtain Si / SiO x and an inner core of an amorphous carbon component;
[0047] S2, shell coating: 30 g of sodium lignin sulfonate was added to 300 mL of 10 wt% starch aqueous solution and dispersed evenly, then the core prepared in S1 was added, and after being evenly dispersed, it was transferred to a high-pressure reactor, and a hydrothermal reaction was carried out at a temperature of 200 ° C and a pressure of 1 MPa for 1 h, filtered, and then carbonized at a temperature of 1200 ° C for 1 h to obtain a composite of a hard carbon-coated core;
[0048] S3, silver doping: add 10g of silver nitrate to 100mL of ethylene glycol solution, prepare an ethylene glycol solution of silver nitrate with a mass volume concentration of 10g / 100mL and use it as a solvent, saturated calomel is used as a reference electrode, and the hard carbon-coated core composite prepared in S2 is pressed on aluminum foil as a working electrode. A constant voltage method (voltage 2V) is used for electrochemical deposition for 600s, followed by washing with 0.1mol / L hydrochloric acid, washing with deionized water, vacuum drying at 80°C for 24h, and crushing to obtain the hard carbon-silicon carbon composite material.
[0049] Comparative Example 1
[0050] 10g of nano-silicon, 10g of hard carbon material (Japan Kuraray, model, Type-5) and 5g of asphalt were mixed evenly and transferred to a ball mill. The mixture was ball-milled at a rotation speed of 100PRM for 24h, followed by vacuum drying for 24h, and then carbonized at a temperature of 800℃ for 3h and crushed to obtain a silicon-hard carbon composite material.
[0051] Comparative Example 2
[0052] S1, preparing the inner core: adding 100 g of nano-silicon to 1500 mL of isopropanol and dispersing the suspension uniformly, then adding 3 g of hexadecyltrimethylammonium bromide and dispersing the suspension uniformly, adjusting the pH to 9 with ammonia water, spray drying, sintering at 800° C. for 3 h under an argon atmosphere, and crushing the suspension to obtain an inner core of Si and amorphous carbon components;
[0053] S2, shell coating: 20 g of sodium lignin sulfonate was added to 400 mL of 5 wt% starch aqueous solution, and then the core prepared in S1 was added. After uniform dispersion, it was transferred to a high-pressure reactor, and a hydrothermal reaction was carried out at a temperature of 150°C and a pressure of 3 MPa for 3 h. The mixture was filtered and carbonized at a temperature of 1000°C for 3 h to obtain a composite of a hard carbon-coated core.
[0054] S3, silver doping: add 10g of silver nitrate to 200mL of ethylene glycol solution to prepare an ethylene glycol solution of silver nitrate with a mass volume concentration of 5g / 100mL and use it as a solvent, saturated calomel is used as a reference electrode, and the hard carbon-coated core composite prepared in S2 is pressed on aluminum foil as a working electrode. The constant voltage method (voltage 2V) is used for electrochemical deposition for 120s, and then it is washed with 0.1mol / L hydrochloric acid, washed with deionized water, vacuum dried at 80°C for 24h, and crushed to obtain the hard carbon-silicon carbon composite material.
[0055] Comparative Example 3
[0056] S1, preparation of the core: 100 g of nano-silicon was added to 1500 mL of isopropanol and dispersed evenly to obtain a suspension, then 150 g of aminopropyltrimethoxysilane and 3 g of hexadecyltrimethylammonium bromide were added and dispersed evenly, the pH was adjusted to 9 with ammonia water, spray dried, sintered at 800 ° C for 3 h, and crushed to obtain Si / SiO x and an inner core of an amorphous carbon component;
[0057] S2, shell coating: prepare 400mL of 5wt% starch aqueous solution, then add the core prepared in S1, disperse evenly, transfer to a high-pressure reactor, perform hydrothermal reaction at a temperature of 150°C and a pressure of 3Mpa for 3h, filter, and carbonize at a temperature of 1000°C for 3h to obtain a composite of a hard carbon-coated core;
[0058] S3, silver doping: add 10g of silver nitrate to 200mL of ethylene glycol solution to prepare an ethylene glycol solution of silver nitrate with a mass volume concentration of 5g / 100mL and use it as a solvent, saturated calomel is used as a reference electrode, and the hard carbon-coated core composite prepared in S2 is pressed on aluminum foil as a working electrode. The constant voltage method (voltage 2V) is used for electrochemical deposition for 120s, and then it is washed with 0.1mol / L hydrochloric acid, washed with deionized water, vacuum dried at 80°C for 24h, and crushed to obtain the hard carbon-silicon carbon composite material.
[0059] Performance tests of the materials prepared in the above examples and comparative examples:
[0060] (1) SEM test
[0061] The hard carbon-silicon carbon composite material prepared in Example 1 was subjected to SEM test, and the test results are as follows: Figure 1 shown.
[0062] Depend on Figure 1 It can be seen that the composite material prepared in Example 1 presents a spherical structure with a uniform size distribution and a particle size of 5-15 μm.
[0063] (2) Physical and chemical properties test
[0064] The composite materials prepared in the examples and comparative examples were tested for particle size, tap density, specific surface area, silver content and interlayer spacing. The silver content was tested by EDS, the interlayer spacing was tested by XRD, and the other test items were tested according to the national standard GBT-24533-2019 "Graphite Anode Materials for Lithium Ion Batteries". The test results are shown in Table 1.
[0065] Table 1
[0066]
[0067] (3) Button battery test
[0068] The composite materials in the embodiment and the comparative example are used as negative electrode materials for lithium-ion batteries to assemble button-type batteries. The specific preparation method of the negative electrode material is: adding a binder, a conductive agent and a solvent to the composite material, stirring and slurrying, coating on a copper foil, drying and rolling to obtain the negative electrode. The conductive agent is SP, and the solvent is double distilled water. According to the composite material: SP: LA132: double distilled water = 95g: 1g: 4g: 220mL, a negative electrode sheet is prepared; a metal lithium sheet is used as a counter electrode; the electrolyte is LiPF 6 / EC+DEC, LiPF in electrolyte 6The electrolyte is a mixture of EC and DEC with a volume ratio of 1:1 as the solvent, and the electrolyte concentration is 1.3 mol / L; the diaphragm is a polyethylene PE film. The button cell is assembled in an argon-filled glove box. The electrochemical performance is carried out on a Wuhan Blue Electric CT2001A battery tester, with a charge and discharge voltage range of 0.00V to 2.0V and a charge and discharge rate of 0.1C. The first discharge capacity and first efficiency of the button cell are tested, and the rate performance (2C / 0.1C) and cycle performance (0.2C / 0.2C, 100 times) are tested at the same time. The test results are shown in Table 2.
[0069] Table 2
[0070]
[0071] As can be seen from Table 1 and Table 2, compared with the comparative example, the first discharge capacity and first efficiency, rate performance and cycle performance of the hard carbon-silicon carbon composites prepared in Examples 1-3 are significantly improved. The reason is that in the present invention, the composite material deposits silver with high electronic conductivity by electrochemical deposition, thereby improving the tap density and its electronic conductivity, thereby improving the material's gram capacity and rate performance. At the same time, the core-shell structured silicon composite-hard carbon composite material is adopted, and the outer hard carbon restrains the expansion of silicon during the charge and discharge process and improves the cycle performance.
[0072] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.
Claims
1. A method for preparing a hard carbon-silicon carbon composite material, comprising the following steps: Preparation of core: Prepare organic solvent dispersion of nano-silicon, add aminosilane coupling agent and dispersant, adjust pH to 8-10 with ammonia water, spray dry, sinter under inert atmosphere, and crush to obtain Si / SiO x and an inner core of an amorphous carbon component; Shell coating: preparing an aqueous solution of sodium lignin sulfonate and starch, adding the prepared core material, dispersing, hydrothermal reaction, filtering, carbonizing, and obtaining a composite of a hard carbon-coated core; Silver doping: Using ethylene glycol solution of silver salt as solvent and saturated calomel as reference electrode, the hard carbon-coated core composite is pressed on aluminum foil as working electrode, and electrochemical deposition is performed by constant voltage method, followed by washing, drying and crushing to obtain the hard carbon-silicon carbon composite material.
2. The preparation method according to claim 1, characterized in that: When preparing the inner core, the mixing ratio of nano silicon, organic solvent, silane coupling agent and dispersant is 100g:1000-2000mL:100-200g:1-5g.
3. The preparation method according to claim 1, characterized in that: The aminosilane coupling agent is selected from at least one of aminopropyltrimethoxysilane, aminopropyltriethoxysilane and aminopropylmethyldiethoxysilane.
4. The preparation method according to claim 1, characterized in that: When coating the shell, the mass ratio of sodium lignin sulfonate, starch and core material is 5-30:5-30:
50.
5. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 100-200°C, the pressure is 1-5Mpa, and the reaction time is 1-6h.
6. The preparation method according to claim 1, characterized in that: The electrochemical deposition time is 60-600s.
7. A hard carbon-silicon carbon composite material, characterized in that: The hard carbon-silicon carbon composite material is prepared by the preparation method according to any one of claims 1 to 6, wherein the hard carbon-silicon carbon composite material has a core-shell structure, and the core comprises Si / SiO x and an amorphous carbon component, wherein the outer shell is hard carbon doped with metallic silver, and the mass percentage of the outer shell is 10-60% based on the total weight of the composite material.
8. The hard carbon-silicon carbon composite material according to claim 7, characterized in that: Based on the total weight of the core, Si accounts for 5-20%, SiO x It accounts for 5-20%, and the rest is amorphous carbon.
9. The hard carbon-silicon carbon composite material according to claim 7, characterized in that: The doping amount of silver is 0.1-0.5% based on the total weight of the composite material.
10. Use of the hard carbon-silicon carbon composite material prepared by the preparation method of claim 1 or the hard carbon-silicon carbon composite material of claim 7 as a negative electrode material for a battery.
Citation Information
Patent Citations
Preparation method of silver doped carbon-silicon composite negative electrode material
CN103151504A
Lithium ion battery, lithium ion battery negative electrode material and preparation method thereof
CN110416515A
Preparation method and application of carbon nanotube-loaded carbon-coated silica material
CN112635734A
Core-shell type silicon-carbon composite material as well as preparation method and application thereof
CN114843482A
Cited By
Hard carbon material coated silicon-carbon composite material and preparation method thereof
CN117038931A
Silicon-based hard carbon composite material and preparation method and application thereof
CN122246105A